SOCS1 is a critical checkpoint in immune homeostasis, inflammation and tumor immunity - Bidgood, Grace M.; Keating, Narelle; Doggett, Karen; Nicholson, Sandra E. (Frontiers in Immunology, 2024)
The Suppressor of Cytokine Signaling (SOCS) family proteins are important negative regulators of cytokine signaling. SOCS1 is the prototypical member of the SOCS family and functions in a classic negative-feedback loop to inhibit signaling in response to interferon, interleukin-12 and interleukin-2 family cytokines. These cytokines have a critical role in orchestrating our immune defence against viral pathogens and cancer. The ability of SOCS1 to limit cytokine signaling positions it as an important immune checkpoint, as evidenced by the detection of detrimental SOCS1 variants in patients with cytokine-driven inflammatory and autoimmune disease. SOCS1 has also emerged as a key checkpoint that restricts anti-tumor immunity, playing both a tumor intrinsic role and impacting the ability of various immune cells to mount an effective anti-tumor response. In this review, we describe the mechanism of SOCS1 action, focusing on the role of SOCS1 in autoimmunity and cancer, and discuss the potential for new SOCS1-directed cancer therapies that could be used to enhance adoptive immunotherapy and immune checkpoint blockade.